2017
DOI: 10.1016/j.amsu.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and diagnostic value of serum intestinal fatty acid binding protein in neonatal necrotizing enterocolitis (case series)

Abstract: ObjectivesIn this study, we aimed to investigate the value of serum intestinal fatty acid binding protein (I-FABP) in early diagnosis and predicting the severity of Necrotizing enterocolitis (NEC).MethodsThis prospective study was performed on 160 preterm neonates ageing less than 35 weeks and weighting less than 2000 gm selected from the Neonatal Intensive Care Units (NICUs) of the Pediatric Department at Benha University hospital and Benha children hospital to evaluate which of them will develop NEC, after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…15 Our results revealed significantly higher I-FABP levels in NEC neonates than in the control group, which was in line with many investigators. 4,26,27 We also noticed that I-FABPp and I-FABPu levels increased according to Bell's staging at the time of diagnosis of NEC. These data were in accordance with other studies.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…15 Our results revealed significantly higher I-FABP levels in NEC neonates than in the control group, which was in line with many investigators. 4,26,27 We also noticed that I-FABPp and I-FABPu levels increased according to Bell's staging at the time of diagnosis of NEC. These data were in accordance with other studies.…”
Section: Discussionmentioning
confidence: 61%
“…These data were in accordance with other studies. 26,29 Also, there were significant positive correlations between IFABPp and IFABPu and between lactate with both IFABPp and IFABPu. In agreement with our findings, Schurink et al 7 emphasized the importance of such biomarkers as indicators of enterocyte damage and compromised intestinal barrier function (increased permeability) that were induced by ischemia and hypoperfusion.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In humans, the FABP-2 gene (IFABP) is located in the chromosomal region 4q28-4q31 and it is only expressed in the small intestine. Because of its specific tissue location, the potential of IFABP as a biomarker of intestinal damage has been explored under a variety of conditions, including celiac disease and necrotizing enterocolitis in premature infants (50)(51)(52). Similarly, the IFABP has been associated with higher intestinal permeability in patients with T2DM, along with the lipopolysaccharide (LPS) and the LPS binding protein (52).…”
Section: Discussionmentioning
confidence: 99%
“…This overall lack of an accurate diagnostic test in early stages of NEC has led to a search for novel diagnostic approaches, which often reflect the downstream pathways that are activated in response to the bacterial-enterocyte signaling mechanisms described above. For instance, Abdel-Haie et al have identified that intestinal fatty acid binding protein (iFABP) can be measured in the serum [46] and urine [47] of neonates with NEC, which was found to have a sensitivity of 90% and specificity of 100%, reflective of the fact that enterocyte death is a natural consequence of disease development after TLR4 activation [46]. Fecal calprotectin -a molecule present in both leukocytes and enterocytes -is elevated in NEC, reflective of the inflammatory pathways that are recruited during NEC pathogenesis [48][49][50][51][52][53][54].…”
Section: New Diagnostic Approaches For Nec and The Bacterial-enterocymentioning
confidence: 99%